A importância da língua inglesa na aprendizagem integral: diálogos e possibilidades a partir de um projeto da disciplina - Brundo, Juliana Castiglia (Universidade do Vale do Rio dos Sinos, 2023)
In the perspective of interculturality, and contextualized and significant experiences, the main objective of this paper is to verify the importance of teaching English in the 11grade of Anchieta School, in Porto Alegre, in the formation of critical and reflexive global citizens. This paper is related to a project that took place in the first trimester of 2023 with the 11th graders in the investigated institution. The methodology that was used was a qualitative survey. For doing so, the secundary data from the manifestations of an evaluative survey, held with 235 students from the 11th grade, was used. A methodology of analyses of data will be presented, and there will be a private interpretation with regard to the perception of the data. The first criteria for the analyses of the data is the validity of its contents, which means the data must be pertinent, adequate, objective and true. Lastly, another important criteria is the description of the data where the meaning of the analized messages is expressed. The theme worked in the English classes to the development of the Project was migration. The theorical foundation was linked between English and Global Citizenship classes. Throughout the survey, it was possible to verify how much the English language can influence in the holistic formation of the students.
Keywords: Cidadania global; Formação integral; Língua inglesa; Global citizenship; Holistic education; English language